In vitro Analysis and Data Comparison of Market Brands of Ciprofloxacin, Ofloxacin and Levofloxacin: Comparison of Ciprofloxacin, Ofloxacin and Levofloxacin Brands (Biological Sciences - PJSIR, 2009)
In the evaluation of three different groups of 12 brands of locally manufactured Quinolone tablets available in the market i.e. ciprofloxacin HCl, ofloxacin and levofloxacin hemihydrate, it was found that composition of active ingredients were within the range of pharmacoepial limits but their disintegration time and rate of dissolution were different, some being very close to the lower pharmacoepial limit. One product was substandard having high disintegration time and very low rate of dissolution.